EXPLORING TRENDS AND FOCUS OF SCIENCE LITERACY RESEARCH: BIBLIOMETRIC ANALYSIS 2019-2024 - Anisa O. S Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze trends and research focuses on science literacy using a bibliometric approach. The research employs bibliometric tools such as VOSviewer and databases like Scopus to map and analyze research trends from 2019 to 2024. Keywords used in this study include "science literacy skills," "science literacy," and "science education." The analysis results show a significant increase in the number of publications related to science literacy over the past decade, with main themes including understanding scientific concepts, developing critical thinking skills, and applying science literacy in social contexts. Additionally, there is a research focus on effective teaching methods and learning strategies that support the development of science literacy across various educational levels. This analysis highlights substantial potential for further research, particularly in linking science literacy with other educational topics and exploring its role in achieving the Sustainable Development Goals (SDGs) for quality education.